(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The translation of science fiction presents distinctive linguistic and cultural challenges due to the genre’s reliance on speculative concepts, technological terminology, and creative language use. Translators often encounter neologisms, invented realities, and culturally embedded references that require flexible and innovative translation approaches. This study explores the primary translation methods and strategies used in translating science fiction texts. Drawing upon established theories in translation studies, the research examines how translators address lexical innovation, maintain narrative coherence, and preserve the imaginative atmosphere of the source text. The findings suggest that effective science fiction translation requires a balanced combination of literal translation, adaptation, borrowing, and creative reformulation to ensure both accuracy and readability.